2019
DOI: 10.32598/bcn.9.10.485
|View full text |Cite
|
Sign up to set email alerts
|

MDMA and the Brain: A Short Review on the Role of Neurotransmitters in the Cause of Neurotoxicity

Abstract: N-Methyl-3, 4-methylenedioxyamphetamine (MDMA), or ecstasy is a recreational drug of abuse. It is a synthetic substance that affects the body's systems, which its mechanism of action and treatment should be more investigated. MDMA provides an immediate enjoyable feeling by stimulating the release of neurotransmitters, such as dopamine and serotonin in the brain. Unfortunately, abnormal regulation of the brain neurotransmitters, as well as the increased oxidative stress causes damage to the brain neurons after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, it is unclear whether the cause is associated with SERT neuron recovery or other causes. Future longitudinal studies are recommended to investigate the serotonin level in blood or cerebrospinal fluid [55] or behavior tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the cause is associated with SERT neuron recovery or other causes. Future longitudinal studies are recommended to investigate the serotonin level in blood or cerebrospinal fluid [55] or behavior tests.…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicated that the SERT self-recovery in rat brain after MDMA-induction was time-dependent and returned to 70.7% ± 3.96% of baseline values at day 28. The regions of low or mid-self-recovery rate were the most affected region by MDMA [4,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the cause is associated with the SERT neurons recovery or other causes. Future longitudinal studies are recommended to investigate the serotonin level in blood or cerebrospinal uid [45] or behavior tests.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, MDMA rebranded as “Ecstasy,” became popular as a recreational drug in the club scene of the 1980's and by 1985 had been designated as a Schedule I compound with high abuse potential without any known medical use ( 14 ). As of 2004, a reported 11 million people in the United States had experimented with MDMA at some point in their lives ( 69 ). By 2011, the number of Americans reporting experimentation with MDMA increased to 14.5 million ( 10 ).…”
Section: Mdmamentioning
confidence: 99%